Ligand‐Free Ullmann‐Type C–Heteroatom Couplings Under Practical Conditions. Issue 15 (14th April 2014) - Güell, Imma; Ribas, Xavi
Abstract: A new practical ligand‐free protocol for copper‐catalyzed C–heteroatom cross‐coupling reactions (Ullmann‐type) is described. The use of dimethyl sulfoxide (DMSO) as the solvent overcomes the need to use organic auxiliary ligands; thus, DMSO is revealed as a nontoxic and superior solvent for Ullmann‐type coupling reactions. This method allows the arylation of a wide range of amides, alcohols, and amines under practical conditions with bromobenzene and iodobenzene derivatives and will likely find direct application in current organic synthesis. The competitive reactivity among different functional groups is reported and rationalized, and the possibility to achieve selective arylation reactions is demonstrated. Abstract : We describe a new easy‐to‐use method for the ligand‐free copper‐catalyzed arylation of amides, alcohols, and amines that affords good cross‐coupling product yields for a wide range of substrates (bromobenzene and iodobenzene derivatives) and nucleophiles.